The clinical method in pediatrics - Luis Hernández Sosa; Sonia Pérez García; María Casanova González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Pediatrics deals with the health care of newborn, children and adolescents and their growing up and development. In order to achieve this purpose it is necessary to make an evaluation of their health condition. The application of the clinical method in children health care is a fundamental tool because it is a system of thoughts implemented to solve problems that may appear when implementing clinical medicine. Nevertheless, it has some particularities, scientific foundations and some art. Children are not young adults, so our medical activities should be oriented according to the age of the patient. The interview, the physical examination and the appropriate parents-patient-doctor relationship are part of the main strategy but it is always related to the age of the child. The objective of all medical interviews is to obtain as much data as possible in order to make a final evaluation of the patient's health condition. In children, there are some differences about the application of the medical interviews' structure, that is why some characteristics of the use of the clinical method in paediatrics are discussed in this article.